Insights into mechanisms of hexavalent chromium removal from aqueous solution by using rice husk pretreated using hydrothermal carbonization technology. Issue 78 (8th August 2016) - Ding, Dahu; Ma, Xin; Shi, Wansheng; Lei, Zhongfang; Zhang, Zhenya
Abstract : Hydrothermal carbonization technique enhanced the adsorption capacity of rice husk towards Cr(vi ). Abstract : A typical agricultural biomass waste, rice husk (RH) was pretreated using simple one-step hydrothermal carbonization (HTC) technology (170–280 °C) and used for hexavalent chromium (Cr(vi )) removal from aqueous solutions. The effects of HTC pretreatment temperature and reaction time on their adsorption capacity towards Cr(vi ) were investigated. Specifically, the mechanisms involved in the removal process were elucidated. According to the results, the optimum pretreatment conditions were found to be 240 °C and 1 h. Adsorption played a much more important role than reduction mechanism. When the solution pH was lower than 3, the adsorption process was suppressed and the reduction process was enhanced. The present results show that the novel HTC pretreated RH is a promising adsorbent for Cr(vi ) removal.